Lymph node yield after rectal resection in patients treated with neoadjuvant radiation for rectal cancer: A systematic review and meta-analysis - Mechera, Robert; Schuster, Tibor; Rosenberg, Robert; Speich, Benjamin (European journal of cancer (1990), 2017)
The lymph node status represents a major prognostic factor in colorectal cancer. However, it was demonstrated that neoadjuvant chemoradiotherapy (CRT) decreases the numbers of lymph nodes in the specimen. Several studies describe less than 12 lymph nodes in the resected specimen of rectal cancer patients after neoadjuvant radiation. This meta-analysis quantifies the influence of neoadjuvant CRT or radiotherapy (RT) only on the lymph node yield in rectal cancer patients. We performed a systematic review and searched PubMed, EMBASE and the Cochrane Library without any language restriction from 1st of January 1980 until 31st March 2015. Two reviewers examined all publications independently and extracted the relevant data if the study assessed lymph node counts or positive lymph node yields of patients who received neoadjuvant treatment compared with patients who did not receive neoadjuvant treatment. Meta-analyses were conducted to quantify the mean difference in lymph node yield. A total of 34 articles (including 37 datasets) were included in the meta-analyses. Neoadjuvant CRT resulted in a mean reduction of 3.9 lymph nodes (95% confidence interval [CI] 3.7–4.1) and an average reduction in harvested positive lymph nodes of 0.7 (95% CI 0.2–1.2) compared with patients who received no neoadjuvant therapy. Individuals who received neoadjuvant RT had, in average, 2.1 lymph node less (95% CI 1.7–2.5) resected compared with their counterparts who received no neoadjuvant treatment. Neoadjuvant CRT or RT only in rectal cancer patients leads to a decrease in lymph node harvest of approximately four and two lymph nodes, respectively. We therefore stress the importance of intensifying all efforts from involved subspecialities (i.e. surgeons and pathologists) to reach the benchmark harvest of 12 resected lymph nodes according to current guidelines. •Neoadjuvant chemoradiotherapy resulted in a mean reduction of 3.9 lymph nodes.•Neoadjuvant radiotherapy resulted in a mean reduction of 2.1 lymph nodes.•Neoadjuvant chemoradiotherapy caused an average reduction in lymph node yield of 0.7.•Neoadjuvant therapy in rectal cancer patients leads to a decrease in lymph node harvest.•All involved subspecialities (i.e. surgeons and pathologists) should intensify their efforts to reach the benchmark harvest of 12 resected lymph nodes.